(x^a+b)^2 (x^b+c)^2 (x^c+a)^2/( x^a*x^b*x^c)^4​

Question

(x^a+b)^2 (x^b+c)^2 (x^c+a)^2/( x^a*x^b*x^c)^4​

in progress 0
Natalia 10 hours 2021-11-25T09:18:56+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-25T09:20:24+00:00

    Step-by-step explanation:

    in above equation, to convert the denominator in terms variable in numerator only, substitute, a+b+c=y

    So, above equation becomes,

    x−a2y−a+x−b2y−b+x−c2y−c=4y

    Just for a the sake of cancelling the denominator terms, substitute x=y2 in this, so we get

    y2−a2y−a+y2−b2y−b+y2−c2y−c=4y

    (y−a)(y+a)(y−a)+(y−b)(y+b)(y−b)+(y−c)(y+c)(y−c)=4y

    (y+a)+(y+b)+(y+c)=4y

    3y+a+b+c=4y i.e. y=a+b+c

    So, this is the same value as per our assumption which is indeed found to be true.

    Hence, x=y2 i.e. x=(a+b+c)2 is the solution of above equation.

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )